2006
DOI: 10.1002/pssc.200565409
|View full text |Cite
|
Sign up to set email alerts
|

Microfabrication of GaN groove on sapphire substrate treated selectively by electron‐beam

Abstract: H 2 -cleaned sapphire substrate was treated with an electron-beam aiming at polarity-selective growth of GaN film by using metalorganic chemical vapor deposition (MOCVD). It was found that GaN growth on the sapphire substrate treated with an electron-beam was suppressed like GaN growth on a SiO 2 mask. GaN grooves having the fluctuated sidewalls were fabricated as designed by lithography patterns due to the selective growth. The groove sidewalls became smoother after etching by dipping in a KOH aqueous solutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2008
2008
2009
2009

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…To solve these problems, we have previously investigated substrate treatment procedures; the sapphire substrate surface was treated and patterned with an electron beam prior to MOCVD growth of GaN [17]. Over the surface areas exposed to electron beam, GaN hardly grows, resulting in groove-like structures with dimensions ranging from micrometer to submicrometers.…”
Section: Introductionmentioning
confidence: 99%
“…To solve these problems, we have previously investigated substrate treatment procedures; the sapphire substrate surface was treated and patterned with an electron beam prior to MOCVD growth of GaN [17]. Over the surface areas exposed to electron beam, GaN hardly grows, resulting in groove-like structures with dimensions ranging from micrometer to submicrometers.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, for patterning process, we employed carbon mask layers to avoid the etching process. 11,12) We have found that this carbon mask layer can be formed onto a sapphire substrate via modification of an organic polymer layer with focused laser irradiation, 11) as well as electron beam exposure. 12) After performing selective growth, this carbon mask layer was removed by thermal treatments, and the re-exposed sapphire surface was nitrided, so that the polarity of GaN was locally inverted during MOCVD growth.…”
mentioning
confidence: 99%